Sharing Medical Profiles for International Students in UUM - Shaladi, Tarek.A.H. (2012)
One of the most common information technology activities is improvement of healthcare and clinical management systems including personal healthcare records. Personal healthcare records have the potential to help individuals to do a more active role in their health care. It plays a main key in medical diagnosis and therapy. International students in UUM do not have personal healthcare records, which can be shared among medical centers. The aim of this study is to develop a prototype for sharing medical profiles; the prototype is developed by using C# language, and the research design based on general methodology. The evaluation was based on user perception through the use of System Usability Scale (SUS), and the prototype was assessed through a sample questionnaire that consists of thirty-three respondents and the results have been positive.